Persistent indebtedness : the need for further action (Commonwealth Secretariat LondonGB, 1987)
Discusses the international debt situation focusing on the relationship between the financial system and debt service, the mechanism for ensuring that the interest on debt is serviced, and the debt problems of low-income countries. Outlines four aspects of the approach to debt management viz. the creation of favourable international economic conditions, rescheduling, greater emphasis on net financial flows to seriously indebted countries under the Baker plan, and adjustment by debtor countries. Proposes a way forward for resolving developing countries debt problems which include inter alia, increased capital flows to developing countries, debt relief, and special arrangements for low-income debtors.
Bibliography: p. 21-22